[Afisz. Incipit:] Nowy wielki film włoski reżyserii Aldo Vergano Słońce wschodzi ... (Gdańsk : [wydawca nieznany], 1948)
Afisz informujący o projekcji filmu.
Keywords: 1901-2000; 1945-1989; Film włoski; Gdańsk (woj. pomorskie); Afisz